Buprenorphine infrequently found in fatal overdose in New York City. (1st October 2015) - Paone, Denise; Tuazon, Ellenie; Stajic, Marina; Sampson, Barbara; Allen, Bennett; Mantha, Shivani; Kunins, Hillary
Highlights: We tested unintentional drug overdose decedents' blood specimens for buprenorphine. Death certificates were linked to toxicology results. Two deaths (2%) were positive for norbuprenorphine but not cause of death. Buprenorphine was infrequently found in drug overdose deaths. Findings suggest that buprenorphine involved overdose is a rare event. Abstract: Background: Buprenorphine is an opioid agonist medication that is both safe and effective in the treatment of opioid use disorders and the prevention of opioid overdoses. Despite this, media coverage has highlighted public concerns about the potential safety consequences of buprenorphine misuse and diversion. To address the possible contribution of buprenorphine to overdose mortality, we systematically tested post mortem blood specimens from decedents who had died of an unintentional drug overdoses in 2013. Methods: We retrospectively tested consecutive drug overdose cases that occurred from June through October 2013. Cases with available blood specimens were tested for buprenorphine and norbuprenorphine using liquid chromatography-tandem mass spectrometry. Toxicology results were linked to death certificates and case files from New York City Vital Statistics and New York City Office of the Chief Medical Examiner. Results: Of the 98 unintentional drug overdose fatalities tested, only 2 (2.0%) tested positive for buprenorphine metabolites. All 98 unintentional fatalities involved multiple substances. Conclusions: Buprenorphine was infrequently found in drug overdose deaths in New York City. Since the safety and efficacy of buprenorphine are well documented, and overdoses resulting from buprenorphine treatment or diversion are very rare, facilitating access to buprenorphine treatment is strongly recommended.